Gastrostomies: experience and complications with three modalities in a tertiary centre over a 26-year period - Piñar-Gutiérrez, Ana; Serrano-Aguayo, Pilar; Gutiérrez, Rocío Vázquez; Rey, Silvia García; González-Navarro, Irene; Tatay-Domínguez, Dolores; Garrancho-Domínguez, Pilar; Remón-Ruiz, Pablo J.; Martínez-Ortega, Antonio J.; Mejías, Verónica Nacarino; Iglesias-López, Álvaro; Socas, María; et al. (Frontiers in Medicine, 2023)
Objectives: To describe and analyze the complications associated with the different gastrostomy techniques (endoscopic (PEG), radiologic (PRG) and surgical (SG) performed in the last 26 years in a terciary hospital.Methods: Retrospective observational study. Patients who underwent gastrostomy at the Virgen del Rocío University Hospital between 1995-2021 were included. For PEG, the PULL technique was performed until 2018 and subsequently the PUSH technique predominantly. For PRG, a pigtail catheter was used until 2003, a balloon catheter between 2003-2009, and a balloon catheter with gastropexy between 2015-2021. For SG, the conventional technique (CSG) was performed until 2009 and since then the laparoscopic assisted percutaneous gastrostomy (PLAG) technique. Descriptive analysis was performed obtaining the median and quartiles of the quantitative variables (P50(P25-P75)) and the frequency for the qualitative variables (n(%)).The comparison of complications between patients who underwent different techniques was performed with Fisher's test.Results: n=1070 (PEG=608, PRG=344, SG=118). The three most frequent indications were head and neck tumors, neurological diseases and gastroesophageal tumors. The percentage of patients who had any complication was 48.9%(PEG-PULL), 23.7%(PEG-PUSH), 38.5%(pigtail PRG), 39.2%(balloon PRG), 29.7% (balloon with gastropexy PRG), 87.3% (CSG) and 41.26%(PLAG). 2(0.18%) patients died from gastrostomy-related complications. 18(1.68%) presented with peritonitis and 5(0.4%) presented with gastrocolic fistula. The rest of the complications were minor. This is a provisional file, not the final typeset article Conclusions: Gastrostomy in any of its modalities is currently a safe procedure with a low rate of complications, most of which are minor.The most frequent complications associated with the administration of enteral nutrition through gastrostomy were minor and the implementation of new techniques in the three modalities has led to a decrease in associated complications. 1 Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos) Código de campo cambiado Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos) Con formato: Fuente: (Predeterminada) Times New Roman, 12 pto Con formato: Fuente: (Predeterminada) Times New Roman, 12 pto Con formato: Interlineado: Múltiple 1,08 lín.